Quality of life of therapies for hormone receptor positive advanced/metastatic breast cancer: Regulatory aspects and clinical impact in Europe. (October 2021) - Moscetti, L.; Sperduti, I.; Frassoldati, A.; Musolino, A.; Nasso, C.; Toss, A.; Omarini, C.; Dominici, M.; Piacentini, F.
Abstract: In recent years, the number of trials incorporating health-related quality of life (HRQoL) data has increased. The impact of HRQoL on regulatory decision making in the European context and on clinical practice is not well established. We conducted an analysis of the role of QoL data extracted from the clinical trials of the drugs approved for hormone receptor positive/HER2-negative advanced/metastatic breast cancer (mBC). The results from the HRQoL were collected and a meta-analysis was performed to evaluate the impact of experimental drugs compared to standard treatments. The results showed a non-detrimental effect in HRQoL from the new treatments. As regards the approval process, from an examination of the European Medicine Agency (EMA) documents, HRQoL was reported nonextensively and contained and discussed in the European assessment reports (EPARs) for eleven trials in the approval process and cited in three cases in the EPARs and summary of medicinal product characteristics (SmPC). An effort should be made by all the stakeholders to increase the visibility of the HRQoL results in order to allow increased consideration in the approval process to make QoL data more easily and visibly available for the clinician and the patients. The evaluation should be reflected in the SmPC in order to increase the amount of information provided to the physician. Highlights: The impact of HRQoL on regulatory decision making in Europe is not well established. PROs allow the patient's perspective to be incorporated in assessing benefits/harms of treatments. HRQoL data are contained/discussed not extensively in EPARs and SmPCs. The meta-analysis on ten trials showed an overall improvement in global QoL. An effort should be made to make QoL data more easily and visibly available.